2020
DOI: 10.1371/journal.pone.0241169
|View full text |Cite|
|
Sign up to set email alerts
|

A mathematical model of COVID-19 transmission in a tertiary hospital and assessment of the effects of different intervention strategies

Abstract: Novel coronavirus (named SARS-CoV-2) can spread widely in confined settings including hospitals, cruise ships, prisons, and places of worship. In particular, a healthcare-associated outbreak could become the epicenter of coronavirus disease (COVID-19). This study aimed to evaluate the effects of different intervention strategies on the hospital outbreak within a tertiary hospital. A mathematical model was developed for the COVID-19 transmission within a 2500-bed tertiary hospital of South Korea. The SEIR (susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…Table VI summarizes the contact parameter in the normal schedule and without break condition. These contact matrices are symmetric, as expected [4]. As explained above in the methods section, the contact parameters of the same category staff are generally increased when the break is omitted from the workflow.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Table VI summarizes the contact parameter in the normal schedule and without break condition. These contact matrices are symmetric, as expected [4]. As explained above in the methods section, the contact parameters of the same category staff are generally increased when the break is omitted from the workflow.…”
Section: Resultssupporting
confidence: 74%
“…The contact rate among the people who are working or receiving treatments in a hospital varies depending on the type of work and hospitalization. Baek, Lee, Cho, Hyun, Kim, Sohn, Kim, Ahn, Jeong, Ku, Yeom, Lee and Choi [4] used the value of contact duration of about 5 hours for the hospital wards and less than 0.5 hours for the outpatient department and emergency room for physicians, nurses, and other caregivers. Patients and caregivers in the hospital wards have the longest contact time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very interesting study from South Korea has recently offered a mathematical model of in-hospital transmission dynamics of COVID-19, and the authors showed how an ‘early testing strategy’ for newly hospitalised patients is effective to reduce nosocomial outbreaks. Notably, while in a low transmission context, the detection of positive patients before admission seems the most important preventive measure, the widespread use of PPE is crucial to control viral transmissibility in high transmission settings [ 8 ]. The effectiveness of universal masking in the in-hospital setting has been also recently strengthened by studies showing that SARS-CoV-2 positivity rates among HCPs were significantly reduced after its implementation; furthermore, even in large hospitals with nearly 10,000 admitted patients, no clear-cut case of in-hospital acquired SARS-CoV-2 infection was registered [ 1 , 8 ].…”
mentioning
confidence: 99%
“…Notably, while in a low transmission context, the detection of positive patients before admission seems the most important preventive measure, the widespread use of PPE is crucial to control viral transmissibility in high transmission settings [ 8 ]. The effectiveness of universal masking in the in-hospital setting has been also recently strengthened by studies showing that SARS-CoV-2 positivity rates among HCPs were significantly reduced after its implementation; furthermore, even in large hospitals with nearly 10,000 admitted patients, no clear-cut case of in-hospital acquired SARS-CoV-2 infection was registered [ 1 , 8 ]. In addition to the triage of suspected cases and PPE use, it was shown that a massive testing strategy, based on nasopharyngeal swabs, to be a third pillar in the control of the pandemic: a group from a highly endemic zone has published its institutional protocol that included molecular testing of all HCPs every 7–10 days, irrespective of their symptoms, and none of the healthcare workers became positive despite being directly in contact with COVID-19 patients [ 9 ].…”
mentioning
confidence: 99%